43.7k views
3 votes
Find the solution to this equation: 3 (2 - 14) +1 = - 4x + 5Remember the steps1. Distribute2. Combine like terms on the left side3. Pick sides variables = constants4. Move terms that don't belong by doing the opposite operations5. Divide if you need to to get x by itself

User Tomas Giro
by
5.1k points

1 Answer

3 votes

Solution

We have the following expression:

3(2-14) +1 = -4x +5

We can distribute and we got:

6 -42+1= -4x+5

We combine like terms on the left side

6-42 +1 -5= -4x

-40 =-4x

And dividing both sides by -4 we got:

x = -40/-4= 10

Then the solution is x=10

User Owen Delahoy
by
4.8k points